Spatial Quality In Collective Housing Transformations And Alterations Made By Residents Of 50 Housing Units In Timgad - Sadeki, Amal; Feloussia, Lahcen (Journal of Architecture and environment of child, 2022)
the alterations made in the interior design at the level of collective housing; is a widespread phenomenon at the level of the Algerian cities. These alterations are very varied in numbers and degrees at different levels. In previous research, several reasons for this phenomenon were found, such as to meet the differences between the granted housing and the real needs and also, lifestyle of Algerian households. The study of 50 social housing units in Timgad city raises questions about: how spaces are transformed in practice and used over time? And why do residents seek to transform the space they occupy at the collective housing? This paper proposes as a study of this phenomenon, which has become a mechanism setting between housing and user, studying the causes and trying to find solutions to meet the needs of households. Then classify the reasons for these transformations for consideration in future designing.